An Analysis on the Infleunce of Relational Benefits on Satisfaction, Commitment and Loyalty (A Survey Done to Gojek Online Transportation Customers) - Rizqy Aziz Basuki; Edy Yulianto; Edriana Pangestuti (Wacana Journal of Social and Humanity Studies, 2019)
This research examined the influence of relational benefits on customer satisfaction, commitment, and loyalty. This research was conducted using a survey design, which samples were selected using a purposive sampling technique. The samples of this research were 357 Gojek Indonesia customers from 10 big cities in Indonesia. Structural Equation Model (SEM) based on Partial Least Square (PLS) was employed as the data analysis tool. The results of this research showed that relational benefits significantly influenced customer satisfaction, commitment and loyalty. Â Customer satisfaction and commitment were also confirmed to abridge the relationship between relational benefit and customer loyalty. Furthermore, customer satisfaction and commitment significantly influenced customersâ€™ loyalty.